Immobilized Enzyme Lipase Catalyzed Transesterification of Olive Oil in Packed Column Reactor - Jenish, S.; Saravanan, K.; Venkatesan, S. (Asian Journal of Chemistry, 2010)
Transesterification reaction was performed using triglycerides and short-chain alcohol by immobilized lipase. Olive oil was used as a substrate for the transesterification reaction. The long-chain fatty acid ester, which is the product of this reaction, can be used as a diesel fuel which doesn't produce sulfur oxide and minimize the soot particulate. Immobilized enzyme lipase from Pseudomonas aeruginosa showed the highest activity in this reaction. Immobilization of lipase was carried out using sodium alginate beads as a carrier. The activity of immobilized lipase was highly increased in comparison with free lipase. Immobilized enzyme could be repeatedly used without troublesome method of separation and the decrease in its activity was not largely observed. The reaction was carried out in a packed column with beads packed to a height of 12 cm. The conversion is very good and the separation of the product is also simple in this enzymatic route. Since the lipase is immobilized it can be used for several cycles and the process is also economical.